2021
DOI: 10.1158/1535-7163.mct-19-0987
|View full text |Cite
|
Sign up to set email alerts
|

A Novel CDK2/9 Inhibitor CYC065 Causes Anaphase Catastrophe and Represses Proliferation, Tumorigenesis, and Metastasis in Aneuploid Cancers

Abstract: Cyclin-dependent kinase 2 (CDK2) antagonism inhibits clustering of excessive centrosomes at mitosis, causing multipolar cell division and apoptotic death. This is called anaphase catastrophe. To establish induced anaphase catastrophe as a clinically tractable antineoplastic mechanism, induced anaphase catastrophe was explored in different aneuploid cancers after treatment with CYC065 (Cyclacel), a CDK2/9 inhibitor. Antineoplastic activity was studied in preclinical models. CYC065 treatment augmented anaphase c… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 53 publications
1
8
0
Order By: Relevance
“…Similar observations have been made in non-malignant and mammary gland breast epithelial cells treated with CYC065 [ 17 ] and THZ1-treated fibroblasts [ 18 ]. In addition, we have shown that CYC065 and THZ1 inhibit the invasive capabilities of these cultures in line with other studies [ 24 , 48 ]. This is key as GBM invasion makes it extremely difficult to surgically resect, which causes high rates of tumour relapse [ 49 ].…”
Section: Discussionsupporting
confidence: 92%
“…Similar observations have been made in non-malignant and mammary gland breast epithelial cells treated with CYC065 [ 17 ] and THZ1-treated fibroblasts [ 18 ]. In addition, we have shown that CYC065 and THZ1 inhibit the invasive capabilities of these cultures in line with other studies [ 24 , 48 ]. This is key as GBM invasion makes it extremely difficult to surgically resect, which causes high rates of tumour relapse [ 49 ].…”
Section: Discussionsupporting
confidence: 92%
“…Recently, CDK family molecules have been used as novel molecular markers for tumor-targeted therapy. As a star molecule, CDK2 ( Kawakami et al, 2020 ) participates in classic pathways in various cancers, such as colorectal cancer ( Somarelli et al, 2020 ), neuroblastoma ( Poon et al, 2020 ), breast cancer ( Hur et al, 2020 ), hepatocellular carcinoma ( Hou et al, 2019 ), and prostate cancer ( Washino et al, 2019 ). However, there are few studies on the mechanism of CDK2 in lung cancer.…”
Section: Discussionmentioning
confidence: 99%
“… 44–49 Enhanced anaphase catastrophe prevented preexisting supernumerary centrosomes from clustering and eradicated aneuploid cancer cells while relatively sparing immortalized bronchial epithelial cells. 44–49 The pan-CDK or selective CDK2 inhibitors seliciclib, 44 dinaciclib, 50 CCT68127 49 and CYC065 (Fadraciclib) 48 each caused anaphase catastrophe. Notably, CCT68127 49 and CYC065 48 that each inhibit CDK2 activity also conferred statistically-significant repression of tumor growth in mice bearing syngeneic or patient-derived xenografts (PDXs) of lung cancers.…”
Section: Introductionmentioning
confidence: 99%
“… 44–49 The pan-CDK or selective CDK2 inhibitors seliciclib, 44 dinaciclib, 50 CCT68127 49 and CYC065 (Fadraciclib) 48 each caused anaphase catastrophe. Notably, CCT68127 49 and CYC065 48 that each inhibit CDK2 activity also conferred statistically-significant repression of tumor growth in mice bearing syngeneic or patient-derived xenografts (PDXs) of lung cancers. CYC065-treatment of these mice led to lung cancers having multipolar or abnormal mitosis.…”
Section: Introductionmentioning
confidence: 99%